2023
DOI: 10.1097/pas.0000000000002117
|View full text |Cite
|
Sign up to set email alerts
|

Positive GPNMB Immunostaining Differentiates Renal Cell Carcinoma With Fibromyomatous Stroma Associated With TSC1/2/MTOR Alterations From Others

Huili Li,
Pedram Argani,
Eitan Halper-Stromberg
et al.

Abstract: Renal cell carcinoma with fibromyomatous stroma (RCCFMS) include ELOC/TCEB1-mutated renal cell carcinoma (RCC) and those with TSC1/2/MTOR alterations. Besides morphologic similarity, most of these tumors is known to be diffusely positive for carbonic anhydrase IX and cytokeratin 7 by immunohistochemistry. We previously showed strong and diffuse expression of GPNMB (glycoprotein nonmetastatic B) in translocation RCC and eosinophilic renal neoplasms with known TSC1/2/MTOR alterations. We retrospectively identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It is also worth noting that GPNMB, a transmembrane protein transcriptionally activated by TFE3/TFEB, has been identified as a significant screening marker not only for MiT translocation RCC but also for TSC/mTOR mutated-associated renal tumors 26,27 . The discovery of recurrent TSC/mTOR mutations in renal HB further promoted us to conduct GPNMB immunohistochemistry to assess its potential as a specific screening marker.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth noting that GPNMB, a transmembrane protein transcriptionally activated by TFE3/TFEB, has been identified as a significant screening marker not only for MiT translocation RCC but also for TSC/mTOR mutated-associated renal tumors 26,27 . The discovery of recurrent TSC/mTOR mutations in renal HB further promoted us to conduct GPNMB immunohistochemistry to assess its potential as a specific screening marker.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, although the routine application of expensive sequencing studies to distinguish between these 2 entities for the presence of underlying ELOC1 or TSC1 / 2 aberrations may not be recommended or clinically feasible, it is prudent to consider or interrogate for the possibility of syndromic associations in such cases. Li et al, 21 in a recent study demonstrated that GPNMB can effectively distinguish RCCFMS with TSC/MTOR alterations from ELOC -mutated RCC and other mimics. In this study, GPNMB was strongly and diffusely positive in all tumors with TSC1/2/MTOR alterations (6/6), whereas negative in all ELOC - mutated RCCs (0/6), or CCPRCTs (0/7) ( P =0.002).…”
Section: Differential Diagnosis Of Renal Tumors With Clear Cytoplasm ...mentioning
confidence: 99%